Membedah Kebijakan India: Analisis Pemberdayaan Pemuda Dalam Kesetaraan Energi - Skolastika Adelia Arianti; Traviata Capella Pringgowijaya (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2026)
In 2003, India introduced the National Youth Policy (NYP) to encourage youth participation across various sectors, including energy. However, more than two decades later, youth involvement in the renewable energy sector remains limited, particularly in advancing energy equality. Energy equality refers to equitable access, affordability, and social justice in energy distribution for all citizens. Although India has made significant progress in renewable energy development due to rapid economic growth, achieving energy equality continues to be a major challenge. This condition affects many communities that still lack fair access to sustainable energy resources. Therefore, this research examines why India’s NYP has failed to optimize the role of youth in achieving energy equality. The study applies the theory of energy justice, which emphasizes the importance of economic incentives, political participation, and social engagement in ensuring energy equality. The findings show that India’s failure stems from limited youth participation and awareness regarding energy issues, inconsistencies between policy implementation and social realities, and inadequate budget allocation for youth empowerment programs in the energy sector.